The Effect of Education by Using Snakes and Ladders as a Medium on Adolescents Knowledge and Attitudes in the Prevention of Premarital Sex in Junior High School - Has, Eka Mishbahatul M; Safitri, Anindita Nayang; Kusumaningrum, Tiyas (International Journal of Psychosocial Rehabilitation, 2020)
Along with the growth and development of adolescents will generate interest in the opposite sex, so it does not rule out the possibility to start dating, which leads to premarital sexual behavior. Adolescents need to be given health education following the characteristics of teenagers who are interested in something new by using snakes and ladders as a medium in providing health education. This study aimed to explain the effect of learning by using snakes and ladders on the knowledge and attitudes of adolescents in preventing premarital sexual behavior. This study method used a quasi-experiment with a pretest-posttest with a control group. The population is the eighth-grade students of Junior High School. The sampling technique used Simple Random Sampling. The number of samples in the study was 36 students, which consisted of a treatment group of 18 students and a control group of 18 students. The research instrument used questionnaires of knowledge and attitudes to prevent premarital sexual behavior. The independent variable in this study was education by using snakes and ladders as a medium, and the dependent variable was knowledge and attitudes. This study applied the Wilcoxon, and Mann-Whitney tests with the significance technique α